Superselective ophthalmic artery infusion of melphalan for intraocular retinoblastoma: preliminary results from 140 treatments. (23rd January 2012) - Venturi, Carlo; Bracco, Sandra; Cerase, Alfonso; Cioni, Samuele; Galluzzi, Paolo; Gennari, Paola; Vallone, Ignazio M.; Tinturini, Rebecca; Vittori, Cesare; De Francesco, Sonia; Caini, Mauro; D'Ambrosio, Alfonso; et al.
Abstract. Purpose: To report our experience in superselective ophthalmic artery infusion of melphalan (SOAIM) for intraocular retinoblastoma. Methods: From June 2008 to October 2010, 38 patients (18 women, 20 men; age range at first treatment, 7 months to 22 years) with 41 eyes with retinoblastoma were scheduled for SOAIM, for 17 newly diagnosed retinoblastomas Tumour, Node and Metastasis (TNM) 7th Edition 1a (n = 1), 1b (n = 1), 2a (n = 7), 2b (n = 4) and 3a (n = 4) and 24 retinoblastomas with partial remission/relapse TNM 7th Edition 1b (n = 13), 2a (n = 1) and 2b (n = 10). Eight patients (ten eyes) have been treated by SOAIM alone. Follow‐up was 6–27 months in 28 patients (30 eyes). Results: Ophthalmic artery cannulation failed in two patients. Thirty‐six patients underwent 140 treatments by internal (n = 112) or external (n = 28) carotid arteries. No major procedural complications occurred. Two patients have been lost to follow‐up. Remaining 34 patients (37 eyes) had no metastatic disease. Four patients suffered permanent ocular complications: chorioretinal dystrophy (n = 2), ptosis (n = 1) and strabismus/exotropia (n = 1). Eight (22%) eyes in eight (24%) patients underwent enucleation: 7/16 (43%) newly diagnosed retinoblastomas and 1/22 (4.5%) retinoblastomas undergoing partial remission/relapse. For all treated eyes, Kaplan–Meier eye enucleation‐free rates (K‐M) were 85.4% (95% CI, 73.3–97.5%), 74.4% (95% CI, 57–91.8%) and still stable at 6, 12 months and 2 years, respectively. For eyes with partial remission/relapse, and eyes at presentation, K–M at 2 years were 95.5% (95% CI, 86.9–100%) and 45.6% (95% CI, 16.6–74.6%), respectively. Conclusion: Superselective ophthalmic artery infusion of melphalan was safe and powerful, especially following other therapies. Superselective ophthalmic artery infusion of melphalan should be added to focal therapies spectrum. In selected cases, melphalan should be combined with other chemotherapeutic agents.